From Anomalies to Essential Scientific Revolution? Intrinsic Brain Activity in the Light of Kuhn's Philosophy of Science - Havlík, Marek (Frontiers in Systems Neuroscience, 2017)
The first step towards a modern understanding of fMRI resting brain activity was made by Bharat Biswal in 1995. This surprising, and at first rejected, discovery is now associated with many resting state networks, notably the famous default mode network (DMN). Resting state activity and DMN significantly reassessed our traditional beliefs and conventions about the functioning of the brain. For the majority of the 20th century, neuroscientists assumed that the brain is mainly the ‘reactive engine’ to the environment operating mostly through stimulation. This ‘reactive convention’ was very influential and convenient for the goals of 20th century neuroscience – noninvasive functional localization based on stimulation. Largely unchallenged, ‘reactive convention’ determined the direction of scientific research for a long time and became the ‘reactive paradigm’ of the 20th century. Resting state activity brought knowledge that was quite different of the ‘reactive paradigm’. Current research of the DMN, probably the best known resting state network, leads to entirely new observations and conclusions, which were not achievable from the perspective of the ‘reactive paradigm’. This shift from reactive activity to resting state activity of the brain is accompanied by an important question: ‘Can resting state activity be considered a scientific revolution and the new paradigm of neuroscience, or is it only significant for one branch of neuroscience such as fMRI?’